Exhaust emission and performance characteristics of coated CI engine fueled with hackberry biodiesel-diesel dual-fuel - Hazar, H.; Telceken, T.; Sevinc, H. (Springer, 2025)
Adopting and maintaining the utilization of alternative fuels in diesel engines depend on lower pollutant emissions and an environmentally friendly fuel. In the present research, exhaust emission and performance parameters of a coated diesel engine running on the hackberry methyl ester (HME) extracted from hackberry seeds were investigated. The engine tests were executed by using a single cylinder, four-stroke diesel engine under a constant load and at different speeds (1800-3000 rpm). The mixtures containing hackberry biodiesel at 20%, 50%, and 100% (vol.) were used in the study. The piston crown and the surface of the valves were coated using a 300-mu m thick Chromium (III) oxide layer. Furthermore, engine block temperatures were acquired. It was determined that hydrocarbon (HC), vibration, exhaust gas temperature (EGT), carbon monoxide (CO), and smoke values lowered; whereas, brake specific fuel consumption (BSFC), brake thermal efficiency (BTE), and nitrogen oxide (NOX) values increased in HME and its fuel blends when compared to diesel fuel. While lower BSFC, CO, smoke, and HC values were detected in the coated engine, lower NOX, BTE, EGT, and vibration values were observed in the uncoated engine.
Keywords: Biodiesel; Hackberry methyl ester; Alternative fuel; Diesel engine; Exhaust emissions